Efficacy of Nigella sativa (Kalongi) for the Treatment of Hyperlipidemia in Sprague Dawley Rats - Kirn-e-Muneera , Muhammad Adnan Saeed , Abdul Khaliq Naveed , Asifa Majeed , Hussain Ali, (Journal of Rawalpindi Medical College, 2013)
Background: To analyze the efficacy of Nigella sativa (Kalongi) for the treatment of hyperlipidemia in Sprague Dawley rats. Methods: Twenty albino rats were divided in two groups. Both groups were fed on ad libitum diets for 02 weeks. Then cholesterol rich diet was given to all rats for 08 weeks followed by treatment with Kalonji for 06 weeks in group II but no treatment in Group I. Blood samples were collected and serum of all rats were analyzed in three phases i.e., at baseline, after cholesterol rich diet and after treatment period for serum cholesterol, serum triglycerides levels, HDLC, LDLC along with serum transaminase levels (ALT). Results: Baseline levels of all parameters were comparable in both groups. The cholesterol rich diet affected all parameters of lipid profile. Nigella sativa (kalonji) showed significant improvement in the lipid profile of rats. The p value < 0.05 of group I and II documented that Nigella sativa (kalonji) had significantly affected the lipid profile as compared to control group. No significant difference was noted in ALT levels between two groups at the end of treatment (p > 0.05). Conclusion: Nigella sativa reduces cholesterol and triglycerides, with adequate safety profile